Organizing science for technology transfer in economic development - Solo, Robert A. (East Lansing: Michigan State University Press, 1975)
The contributions of a rich, technically advanced country intended to raise the level of productivity in a poor, technically backward one will be referred to as AID. The interest of this book is in one aspect of technical assistance, namely, the use of donors of their scientists, research centers, and other science-based organizations. Hence, the book has to do not only with AID but also with government policies related to the use of science resources- hence, with science policy.
Includes bibliographical references and index.
ne 11/04/2018
Loans
Keywords: Technical assistance; Technology transfer; Science and state; Technology transfer - economic development